Political Branding Analysis of Prabowo-Sandiaga in Terms of Appearance and Personality Aspects (Study on the 2019 Election) - Alvin Gumelar Hanevi; Suryanef Suryanef; Al Rafni (CV. Rayyan Dwi Bharata, 2002)
This research was conducted to analyze the political branding of the presidential and vice-presidential candidates Prabowo and Sandiaga from the appearance and personality aspects of the study in the 2019 election. In the presidential election contest, there were many ways and strategies used by each pair of presidential and vice-presidential candidates. compete. This study aims to describe Prabowo and Sandiaga's political branding in two aspects: appearance and personality. This type of research is qualitative and descriptive in nature. Informants in this study came from members of the Gerindra Party DPD management and community elements. From the results of the study, it was found that the personality and performance of Prabowo and Sandiaga were very different, the figure of Prabowo in terms of personality was a figure who was assertive, tough, and nationalist, while from the performance aspect the figure of Prabowo was seen as a figure of struggle, a figure who firmly fought for the interests of the people. As for Sandiaga's figure, from the personality aspect, he is a millennial intelligent and well-mannered figure, while from the performance aspect, Sandiaga is a figure who is always close to millennials and close to women, especially among mothers.